Anti-CCR4 treatment depletes regulatory T cells and leads to clinical activity in a canine model of advanced prostate cancer. Issue 2 (7th February 2022) - Maeda, Shingo; Motegi, Tomoki; Iio, Aki; Kaji, Kenjiro; Goto-Koshino, Yuko; Eto, Shotaro; Ikeda, Namiko; Nakagawa, Takayuki; Nishimura, Ryohei; Yonezawa, Tomohiro; Momoi, Yasuyuki
Abstract : Background: Targeting regulatory T cell (Treg) infiltration is an emerging strategy for cancer immunotherapy. However, its efficacy in advanced prostate cancer remains unclear. Here, we showed the therapeutic efficacy of anti-Treg treatment in a canine model of advanced prostate cancer. Methods: We used dogs with naturally occurring prostate cancer to study the molecular mechanism underlying Treg infiltration and the effect of anti-Treg treatment. Tumor-infiltrating Tregs was evaluated by immunohistochemistry, and the association with prognosis was examined in dogs with spontaneous prostate cancer. The molecular mechanism of Treg infiltration was explored by RNA sequencing and protein analyses. A non-randomized canine clinical trial was conducted to define the therapeutic potential of anti-Treg treatment for advanced prostate cancer. Human prostate cancer datasets were analyzed to compare gene expression in dogs and humans. Results: Tumor-infiltrating Tregs were associated with poor prognosis in dogs bearing spontaneous prostate cancer. RNA sequencing and protein analyses showed a possible link between the CCL17–CCR4 pathway and the increase of tumor-infiltrating Tregs. Dogs with advanced prostate cancer responded to mogamulizumab, a monoclonal antibody targeting CCR4, with decreased circulating Tregs, improved survival, and low incidence of clinically relevant adverse events. Urinary CCL17 concentration and BRAF V595E mutation were independently predictive of the response to mogamulizumab. Analysis of a transcriptomic dataset of human prostate cancer showed that the CCL17–CCR4 axis correlated with Foxp3. In silico survival analyses revealed that high expression of CCL17 was associated with poor prognosis. Immunohistochemistry confirmed that tumor-infiltrating Tregs expressed CCR4 in human patients with prostate cancer. Conclusions: Anti-Treg treatment, through CCR4 blockade, may be a promising therapeutic approach for advanced prostate cancer in dogs and some population of human patients.